STUDI KONVERSI TPA RAWA KUCING KE RUMAH PRODUKSI SAMPAH - Asep Sugara (Gapenas Publisher, 2021)
The inherent assumption of every human being is that waste is something useless. As long as this assumption persists in the human mind, the waste problem will continue to exist, even though various methods (technology) and regulations are issued. This study describes qualitatively the impact of waste management at the Rawa Kucing landfill in Tangerang City on the development of the area and carries out the reconstruction of a change in perspective on waste and the conversion of Rawa Kucing into a waste production house